TYPOLOGY OF REGIONS ACCORDING TO THE LEVEL OF FOOD SECURITY: METHODOLOGICAL APPROACHES AND SOLUTIONS - Elena DERUNOVA; Natal’ya KIREEVA; Olesya PRUSCHAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article deals with the problems of significant differentiation of the regions of Russia in terms of food security, which poses a threat to sustainable regional development and can lead to serious socio-political risks in the functioning of the national food system. Methodological approaches to the typology of regional agri-food systems based on a set of various criteria and indicators of food security, including independence, physical and economic accessibility of food, as well as stability of development, are proposed. It is proved that the use of criterion of food independence in the model of food security is appropriate only for development of the national food system. However, for regional agri-food systems, physical and economic accessibility of food for all population groups and stability of functioning of agri-food systems are of paramount importance. The degree of differentiation of individual RF subjects in terms of non-compliance with food safety criteria was evaluated, which made it possible to identify regions vulnerable to food security. The developed methodological and methodical provisions can serve as a basis for making management decisions in the field of food safety at the federal and regional levels.